2011
DOI: 10.4028/www.scientific.net/amr.356-360.2892
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Water Resource in Taiyuan, China Using HJ-1B Imagery

Abstract: Remote sensing technology can be used to quickly extract macro information of the study area, and its advantages in monitoring water resources have become increasingly evident. In this study, Fenhe 2nd reservoir and Jinyang Lake in Taiyuan,Shanxi Province were examined using the remote sensing data obtained from HJ-1B on May 6, 2010. Water area of Fenhe 2nd reservoir was extracted using NDWI and improved segmentation threshold. The distribution of eutrophication and phytoplankton in Jinyang Lake were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The solution consists of a liquid or dry powder that is diluted in water and primarily acts to reduce friction between media, flush soil and debris from the bowl, and to form a rust inhibiting layer on finished part surfaces [6]. Development of media and compound primarily depends on experiments, effects of surface roughness and material removal with different media parameters have been done to practical application [2,46,[49][50]. Some compounds are based on organic substances, which are almost completely biodegradable [39].…”
Section: Equipments and Consumablesmentioning
confidence: 99%
“…The solution consists of a liquid or dry powder that is diluted in water and primarily acts to reduce friction between media, flush soil and debris from the bowl, and to form a rust inhibiting layer on finished part surfaces [6]. Development of media and compound primarily depends on experiments, effects of surface roughness and material removal with different media parameters have been done to practical application [2,46,[49][50]. Some compounds are based on organic substances, which are almost completely biodegradable [39].…”
Section: Equipments and Consumablesmentioning
confidence: 99%
“…Despite the wide use of the D-S theory, scholars observed that classical D-S theory unable to produce reasonable outcome in case of paradoxes (because of complication of realistic environment and probable conflicts of sources of evidence) [32]. Therefore DCR is improved previously before its application in this paper.…”
Section: Introductionmentioning
confidence: 99%